Dakwah Keluarga: Internalisasi Nilai-nilai Budi Pekerti dalam Keluarga Jawa - Nawawi, Nawawi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2012)
This study focused on the system of social organization, the internalization process in the family, phases of the internalization, values are internalized Java manners and internalization models used. The purpose of this study to determine the implementation process of internalization, its phases, values and manners Java internalization models used. The research was conducted in three families in Bonjokmangir Java. The interpretive techniques used to analyze the values contained in the manners of the three families of Java. This study uncovered three families in the internalization process Bonjokmangir, values and manners Java internalization models used. Character values include the principles of Java respectful, harmonious life, honesty, introspection, sincere and selfless, mindful character, manners, ngati-ati, nrima and resigned. Internalization stage there are three phases namely the unborn baby through childhood, during adolescence and adulthood period. Internalization models used a model of democracy, exemplary models, wayang model fitting and communication model using the Java language and manners in the family associate.